THE LEGAL AND REGULATORY ASPECTS OF INTERNATIONAL REMITTANCES AND THEIR IMPACT ON MIGRANT WORKERS AND ASYLUM SEEKERS IN SOUTH AFRICA - Vivienne Lawack (Obiter, 2014)
South Africa, being a relatively politically and economically stable African nation, offers numerous pull factors making it an attractive destination for many African, as well as international, migrants. Migrants usually leave their countries of origin to seek work opportunities in other countries. Regardless of the legality of work, migrants find the need to send money to families they have left in their country of origin. When such a need arises, the migrant worker, the low-income migrant worker in particular, often faces considerable legal as well as financial obstacles in accessing the services of formal financial institutions such as banks. As a consequence, they may have to rely on informal means to send their funds. There are numerous factors that may drive the preference for informal markets, such as cost factors and other payment-system issues. However, this analysis examines how legal and regulatory provisions impact upon the international remittance industry in South Africa and the ability of the low-income migrant worker to access formal remittance services.